2019
DOI: 10.32098/mltj.01.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of prolotherapy for intra-tendinous Achilles tears: a case series

Abstract: Background:The intra-tendinous tear is a new pathology that is defined as a discontinuity of fibres situated entirely within the tendon. Prolotherapy involves injecting an irritant, such as hyperosmolar dextrose, to stimulate a tissue healing response and ultimately reduce pain. Methods: 43 consecutive patients diagnosed with an intra-tendinous tear were included (27 males: 16 females, mean (SD) age 41 (11.3). Patients were injected with 0.4ml-1.5ml (mean 0.8ml) of 50% dextrose and 0.5% marcaine mixed in a 1:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In general, an immobilization of the treatment sites after PRP therapy was recommended or ordered in order to escape the inhibition or the delay of the cellular reparative reactions in clinics for human (28). The present study demonstrated that tendinopathies recovered well in P75 or P100 groups without the immobilizations of the treatment sites after PRP therapy, suggesting that tendinopathies in human might also recover well by the PRP therapy under the condition that the concentrations of platelets in PRP were in the optimal range even though without immobilizations of the treatment sites.…”
Section: Discussionmentioning
confidence: 99%
“…In general, an immobilization of the treatment sites after PRP therapy was recommended or ordered in order to escape the inhibition or the delay of the cellular reparative reactions in clinics for human (28). The present study demonstrated that tendinopathies recovered well in P75 or P100 groups without the immobilizations of the treatment sites after PRP therapy, suggesting that tendinopathies in human might also recover well by the PRP therapy under the condition that the concentrations of platelets in PRP were in the optimal range even though without immobilizations of the treatment sites.…”
Section: Discussionmentioning
confidence: 99%
“…There are nine studies (52%) used the concentration of dextrose with 25% [8,9,12,14,16,17,22,23,28] while three studies each used concentrations with 20% [11,15,18] or 15% [19][20][21]. The other two studies used concentrations of 10% [23] and 16.5% [13].…”
Section: Concentration Of Dextrose and Injection Protocolmentioning
confidence: 99%
“…The other two studies used concentrations of 10% [23] and 16.5% [13]. Most of study (15 studies/88%) reported dextrose mixed with lidocaine, and only one study used a mix with saline [8] or marcaine [28].…”
Section: Concentration Of Dextrose and Injection Protocolmentioning
confidence: 99%
“…Anecdotally, this is not something we have discovered. Research into suggested treatment techniques have already been undertaken 32 . Despite this study being retrospective, the Authors did have the benefit of saved images and videos when compiling the data, along with the ultrasound reports.…”
Section: Future Research and Limitationsmentioning
confidence: 99%